Business Communication Strategy Fritz Gelato through Instagram - Putraruri, Clement; Inggrid; Anyelia, Evira Dwi (GoAcademica Research & Publishing, 2024)
The enormous business competition in this era also forces every business to be able to adapt to technology. With the advent of technology, and competition, activities such as marketing and recruitment information carried out by businesses are moving from print to online media. This proves the important role of social media in the digital era, which is very important in developing a business so that it continues to run. This research focuses on business communication strategy as a tool for Fritz Gelato to introduce and promote his business to the wider community with the help of technology. This research aims to find out the role of Fritz Gelato's business strategy which utilizes communication in helping the development of the business itself. The qualitative method used in this research uses business communication strategies to see how important communication is in business development. This research found that communication in business can provide higher business exposure to Fritz Gelato, which can provide information access to customers more easily and increase a business's credibility.